Experience of the Organization of the Front-Rear Provision and Moral and Spiritual Provision of Federal Troops of the Russian Federation in Combat Actions - Beknazarov Asqar Sabitovich (European Science Publishing, 2023)
In this article, the experiments of the federal troops of the Armed Forces of the Rossiy Federation on the organization of the front-rear supply and moral-mental supply in combat actions in the North Caucasus region, shortcomings in the organization of the front-rear supply and moral-mental supply in combat actions and the analysis of organization and conduct, conclusions are discussed.
Keywords: Federal troops, troops supply, food supply, fuel consumption standard, practical experience, moral-mental supply, moral-mental state.